Fit to practice empire, race, gender, and the making of British medicine, 1850-1980 - Haynes, Douglas Melvin (Rochester studies in medical history, 2017)
Traces the history of the British General Medical Council to reveal the persistence of hierarchies of gender, national identity, and race in determining who was fit to practice British medicine